Taxonomy and biogeography of the Pleistocene New Zealand sea lion Neophoca palatina (Carnivora: Otariidae). (16th June 2016) - Churchill, Morgan; Boessenecker, Robert W.
Abstract: The Otariidae (fur seals and sea lions) are an important and highly visible component of Southern Hemisphere marine mammal faunas. However, fossil material of Southern Hemisphere otariids is comparatively rare and often fragmentary. One exception is the Pleistocene sea lion Neophoca palatina King, 1983a, which is known from a nearly complete skull from the North Island of New Zealand. However, the phylogenetic affinities of this taxon are poorly known, and comparisons with other taxa have been limited. We provide an extensive redescription of Neophoca palatina and diagnose this taxon using a morphometric approach. Twenty measurements of the skull were collected for N. palatina, as well as for all extant Australasian otariids and several fossil Neophoca cinerea Perón, 1816. Using principal component analysis, we were able to segregate taxa by genus, and N. palatina was found to cluster with Neophoca according to overall size of the skull as well as increased width of the intertemporal constriction and interorbital region. N. palatina can be distinguished from all other Australasian otariids by its unusually broad basisphenoid. Discriminant function analysis supported referral of Neophoca palatina to Neophoca with very high posterior probability. These results confirm the treatment of Neophoca palatina as a distinct species of Neophoca and highlight the former broad distribution and greater tolerance for colder temperatures of this genus. These results also suggest that New Zealand may have played a pivotal role in the diversification of Southern Hemisphere otariid seals.